Prevention of OprD regulated antibiotic resistance in Pseudomonas aeruginosa biofilm. (November 2017) - Raavi; Mishra, Swechha; Singh, Sangeeta
Abstract: In P.aeruginosa biofilms, the issue of antibiotic resistance is of particular importance due to increasing number of infections being reported in medical implants. The current study is focused on CzcR and CopR proteins which are part of two-component signal transduction systems (TCSs) - CzcR–CzcS and CopR–CopS respectively in P.aeruginosa . They both negatively regulate OprD porin expression which affects the intake of antibiotics like carbapenems. These two proteins can be treated as targets to combat antibiotic resistance in P.aeruginosa. Docking was performed on these proteins in search of inhibitors against the CzcR–CzcS and CopR–CopS TCSs. Efficient inhibitory ligands were evaluated on the basis of least binding energy, human oral absorption and ADME properties using a four-tier structure based virtual screening. The resulting ligands displayed high effective inhibitory property and satisfactory pharmacokinetics as compared to inhibitors which have been identified before for two-component signal transduction systems for gram negative bacteria. These potential inhibitors can now be used further in wet lab by performing selectivity assays to determine their inhibition rate against P.aeruginosa biofilms. Identification of potential leads may enable the development of new therapeutic strategies aimed at disrupting P.aeruginosa biofilms. Highlights: The effectiveness of various ligands against the protein structure of CzcR and CopR. Insilico screening against these proteins. Simulation studies for stability check.